DAMPAK MERGER DAN AKUISISI TERHADAP KINERJA KEUANGAN PERUSAHAAN - Mia Kurniati; Asmirawati Asmirawati (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract This study aims to analyze the impact of mergers and acquisitions on the financial performance of publicly traded companies listed on the Indonesian stock exchange that conducted mergers and acquisitions from 2006 to 2015. This study uses six financial ratios, namely return on equity (ROA), net profit margin (NPM), quick ratio (QR), debt to asset ratio (DAR), total asset turn over (TATO) and price earning ratio (PER). The analytical method used in this research is nonparametric analysis using the Wilcoxon rank test. The Wilcoxon rank test is a nonparametric analysis that compares two paired samples. This study compares the company's financial performance one year before mergers and acquisitions with one year after mergers and acquisitions. The results showed that there were significant differences in the ROA and NPM values. Then on the values ​​of QR, DAR, TATO and PER there is no significant difference between before and after mergers and acquisitions.